Implementasi Algoritma Backtracking pada Penyelesaian Sudoku: Studi Kasus dan Evaluasi Kinerja - M. Zakiansyah; Dzikri Thoriq Al Ariiq; Tata Sutabri (Jurnal Manajemen Informatika & Teknologi, 2025)
Sudoku is a 9x9 grid-based number logic puzzle that requires filling in digits from 1 to 9 uniquely in each row, column, and 3x3 subgrid. This study implements the backtracking algorithm as a systematic solution-searching method for solving Sudoku puzzles automatically. The implementation is done using Python, and performance is evaluated based on puzzles of varying difficulty levels. The analysis focuses on execution speed and memory efficiency. The results indicate that backtracking performs effectively for easy and medium-level puzzles but experiences significant performance drops with more complex puzzles. This research provides a measurable overview of the backtracking algorithm’s performance in solving Sudoku.